Strategi Pengembangan Bakso Mercon Pak Rahmat Di Kekalek Jaya Kecamatan Sekarbela - Alvieno Dwi Cahyo Putra; Baiq Ertin Helmida; Erviva Farianti (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2025)
The purpose of this study was to determine the development strategy of Pak Rahmat's Mercon Meatballs in the Kekalek Jaya area, Sekarbela District. There are several fundamental problems that cause Pak Rahmat's meatballs to have difficulty developing, including in the human resources, capital, marketing and technology sectors. The population in this study was Bakso Mercon Kekalik Jaya. The research sample is Bakso Mercon Pak Rahmat. This research uses qualitative methods with primary data collection, namely using interviews, observation and documentation. The data analysis technique used is SWOT analysis technique and SWOT matrix as the formation of the right strategy to use. The results of this study indicate that the continuity of Pak Rahmat's mercon meatballs is more likely to survive and does not have the ability to develop a meatball business.